Diseño de completación dual concéntrica bes- fn para casing de 9 5/8 - Soto Almeida, Joao Carlos (2009)
The purpose for this project is to develop a dual concentric completion where we´re going to produce two stratus. The sand “U down” will produce using ESP due to the characteristics of the fluid and the production level. The sand “Upper Hollin” will be produced using Natural Flow because the reservoir characteristics. It covers the petrophysics characteristics, the properties of the fluids, a geological resume about the Amazonian region and the basins, so that will help to understand the lithology and the reservoir shape where the completion will be designed. There is an explanation and description about the dual completion systems and tools needed to design it. This also shows a detailed description of the bottom hole assembly, the procedures and the criterions for selecting the tool and all the equipments according of the characteristics of the well and the reservoir. The final part has a detailed analysis of all the expenses such as: tool, equipments, rent of rig, operation cost, installation cost, etc. there is also a analysis cost-benefit and show the IRR and NPV which help us to know that our project is profitable.